Islam di Filipina, Perkembangan Islam dan Pengaruhnya di Era Modern - Ramlianto; Agil Husain Abdullah; Syamsudhuha Saleh; Bahaking Rama (PT. AHLAL PUBLISHER NUSANTARA, 2025)
This study examines Islam in the Philippines by focusing on the development of Islam and its influence in the modern era. The study aims to analyze the historical dynamics of Islam, the role of Islamic education, and the social influence of Islam within the context of Muslim minority communities in the Philippines. A qualitative approach with a historical method was employed through library research. Data were analyzed using qualitative descriptive techniques by interpreting sources related to Islamic history, education, and thought in the Philippines. The findings indicate that Islam in the Philippines has developed in an adaptive and contextual manner through the strengthening of Islamic education, dynamic religious thought, and social and humanitarian activities. Islam plays a significant role in preserving religious identity while promoting social integration within modern Philippine society. AbstrakPenelitian ini membahas Islam di Filipina dengan fokus pada perkembangan Islam dan pengaruhnya di era modern. Kajian ini bertujuan untuk menganalisis dinamika historis Islam, peran pendidikan Islam, serta pengaruh sosial Islam dalam konteks masyarakat Muslim minoritas di Filipina. Penelitian menggunakan pendekatan kualitatif dengan metode historis melalui studi kepustakaan. Analisis data dilakukan secara kualitatif-deskriptif dengan menafsirkan berbagai sumber terkait sejarah, pendidikan, dan pemikiran Islam di Filipina. Hasil penelitian menunjukkan bahwa Islam di Filipina berkembang secara adaptif dan kontekstual melalui penguatan pendidikan Islam, pemikiran keagamaan yang dinamis, serta aktivitas sosial dan kemanusiaan. Islam berperan penting dalam menjaga identitas keagamaan sekaligus mendorong integrasi sosial umat Islam di tengah masyarakat Filipina modern.